Pengaruh Pendidikan Karakter, Budaya Sekolah, dan Keterampilan Mengajar Guru Terhadap Prestasi Belajar Siswa Di MAN 2 Banyumas - Mawar Karissa (Economic Education and Entrepreneurship Journal, 2021)
This research is categorized as quantitative research with a survey method at MAN 2 Banyumas. This study aims to analyze: (1) The effect of character education on student achievement at MAN 2 Banyumas; (2) The influence of school culture on student achievement in MAN 2 Banyumas; (3) The effect of teacher teaching skills on student achievement in MAN 2 Banyumas; (4) The influence of character education, school culture and teacher teaching skills on student achievement in MAN 2 Banyumas. This study used a population of students of class X, XI, Science and Social Sciences at MAN 2 Banyumas with 848 students. As for this study, for taking samples using random numbers so that a total of 170 students were obtained. This study uses multiple regression analysis, classical assumption test, F test, t-test, and coefficient of determination. Based on the results of research and data analysis with the SPSS 23 program, it shows that: (1) There is a positive influence between character education on student achievement at MAN 2 Banyumas; (2) There is a positive influence between school culture on student achievement in MAN 2 Banyumas; (3) There is a positive influence between teacher teaching skills on student achievement in MAN 2 Banyumas; (4) There is a positive influence between character education, school culture, and teacher teaching skills on student achievement in MAN 2 BanyumasKeywords: Character Education, School Culture, Teacher Teaching Skills, Learning Achievement